Are Our FEERs Justified? - Barisone, G; Driver, R; Wren-Lewis, S (2006)
The Fundamental Equilibrium Exchange Rate (FEER) method of calculating an equilibrium real exchange rate is the most widely used alternative to PPP. This paper presents the first comprehensive historical test of FEER calculations for six major economies, using estimates for the last 20 years. We focus on unit root and cointegration techniques both at the individual country level and jointly using panel based estimation. Specifically, we test whether real exchange rates cointegrate with time series for the FEER. Even at an individual country level, the results provide support for the FEER, particularly in Canada, the UK and Germany. Panel unit root tests suggest that the real exchange rate and FEER cointegrate. Overall the results suggest that the FEER approach represents an improvement over PPP in explaining medium- to long-term trends in the real exchange rates of the major industrialised countries.